The impact of economic factors on the profitability and market share of Syrian insurance companies - بلدية, علاء; يمن منصور (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study dealt with economic factors and their impact on the profitability and market share of insurance companies, because the insurance sector is one of the sectors that support the local economy of any country, due to the vitality of this sector in the process of collecting capital, saving and investing, through a questionnaire that was distributed to a number of workers in The insurance sector, which included questions about income averages, the activities of insurance companies and their services. The questionnaire was analyzed using the SPSS program and appropriate statistical tests were used, such as the one sample Test. Through this study, we found that there is a statistically significant effect of economic factors such as average per capita income, high unemployment rates, inflation rates, economic stagnation, interest rates, and quality of services on the profitability of insurance companies and their market share.